1996
DOI: 10.1136/jnnp.60.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of positron emission tomography, cognition, and brain volume in Alzheimer's disease with and without severe abnormalities of white matter.

Abstract: Objectives-To examine cerebral metabolism, cognitive performance, and brain volumes in healthy controls and two groups of patients with probable Alzheimer's disease, one group with severe abnormalities of white matter (DAT +) and the other group with none, or minimal abnormalities (DAT -). Methods-Neuropsychological tests, CT, MRI, quantitative MRI, and PET studies were carried out to allow comparison between the DAT + and DAT -groups and the healthy controls. Results-Compared with the healthy controls, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 46 publications
2
57
0
1
Order By: Relevance
“…It is interesting that the bivariate association between DelRec and the log-transformed WMH variable is significant in normals since some previous studies have also found significant associations between cognition and WMH in healthy elderly (DeCarli et al, 1995;Swan et al, 1998Swan et al, , 2000 while some have not (DeCarli et al, 1996;Kozachuk et al, 1990;O'Brien et al, 1997). A more limited range of WMH in normals may have contributed to these conflicting findings (Gunning-Dixon & Raz, 2000).…”
Section: Wmh and Declarative Memorymentioning
confidence: 54%
See 1 more Smart Citation
“…It is interesting that the bivariate association between DelRec and the log-transformed WMH variable is significant in normals since some previous studies have also found significant associations between cognition and WMH in healthy elderly (DeCarli et al, 1995;Swan et al, 1998Swan et al, , 2000 while some have not (DeCarli et al, 1996;Kozachuk et al, 1990;O'Brien et al, 1997). A more limited range of WMH in normals may have contributed to these conflicting findings (Gunning-Dixon & Raz, 2000).…”
Section: Wmh and Declarative Memorymentioning
confidence: 54%
“…A more limited range of WMH in normals may have contributed to these conflicting findings (Gunning-Dixon & Raz, 2000). However, the specific association between episodic memory and WMH is significant but rather weak in several studies (DeCarli et al, 1995;Libon et al, 1998;Ylikoski et al, 1993) and a recent meta-analysis (Gunning-Dixon & Raz, 2000) suggesting a weak association in the more commonly studied groups of AD patients and normals (DeCarli et al, 1996;Swan et al, 2000;Ylikoski et al, 1993).…”
Section: Wmh and Declarative Memorymentioning
confidence: 98%
“…3,4 Those with AD and WMHI show greater visuospatial dysfunction, 5 attention/concentration impairment, 6 slower cognitive processing, and greater executive dysfunction 6 than those with AD alone, but other studies find no neuropsychological differences between these 2 groups. [7][8][9] Functional imaging studies show different activation patterns in those with and without WMHI, suggesting that an equivalent level of cognitive impairment results from different mechanisms in AD with and without WMHI. 7,10 In contrast to subtle and often controversial cognitive correlates of CVD-related MRI hyperintensities, MRI measures of atrophy have shown stronger and more consistent relationships with cognitive impairment.…”
mentioning
confidence: 99%
“…White matter hyperintensity on MR imaging and lacunar infarction may contribute to reduction in cerebral blood flow and glucose metabolism (DeCarli et al, 1996;Miyazawa et al, 1997). Several studies tried to identify distinctive patterns for vascular dementia on FDG-PET, but due to the limitations of the visual method on FDG-PET, no definitive finding could be obtained (De Reuck et al, 1998;Mielke et al, 1994;Sultzer et al, 1995).…”
Section: Vascular Dementiamentioning
confidence: 99%